Food politics : what everyone needs to know - Paarlberg, Robert L. (Oxford University Press, 2010)
Examines the politics of food, discussing convenience foods, under-regulated commercial farms, backlash against environmentalists and consumer activists, agricultural failure in third world countries, and other related topics.